Forest Genetic Resources training guide - Boshier, D.; Bozzano, M.; Loo, J.; Rudebjer, P.G.; Bioversity International (2014)
This set of training materials enables teachers and trainers to cover forest genetic resources issues in their courses and increase understanding of how to manage diverse and complex forest and other tree based ecosystems sustainably. The training guide covers practical issues that practitioners confront in real-life, introduces students to basic genetic concepts and shows their relevance and application to these real issues. Organized in a modular format, the guide provides case studies, teacher notes and audiovisuals that are flexible and easy to use in a range of formal or informal training and learning situations. Access the guide here